2021
DOI: 10.1021/acsami.1c15560
|View full text |Cite
|
Sign up to set email alerts
|

Quasi-Epitaxial Growth of β-Ga2O3-Coated Wide Band Gap Semiconductor Tape for Flexible UV Photodetectors

Abstract: The epitaxial growth of technically-important β-Ga2O3 semiconductor thin films have not been realized on flexible substrates due to limitations by the high-temperature crystallization conditions and the lattice-matching requirements. In this report, for the first time single crystal β-Ga2O3 (-201) thin films is epitaxially grown on the flexible CeO2 (001)-buffered hastelloy tape. The results indicate that CeO2 (001) has a small bi-axial lattice mismatch with β-Ga2O3 (-201), thus inducing a simultaneous double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
32
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 77 publications
0
32
0
Order By: Relevance
“…β-Ga 2 O 3 has a high breakdown electric field strength of 8 MV/cm and exceptional Baliga figure of merit (BFOM) and Johnson’s figure of merit (JFOM) due to ultrawide bandgap of 4.6–4.9 eV, much higher than those of SiC and GaN. β-Ga 2 O 3 has a high saturation electron velocity ( v s ) of 2 × 10 7 cm/s, which allows for high current density and high-frequency operation. , …”
Section: Introductionmentioning
confidence: 99%
“…β-Ga 2 O 3 has a high breakdown electric field strength of 8 MV/cm and exceptional Baliga figure of merit (BFOM) and Johnson’s figure of merit (JFOM) due to ultrawide bandgap of 4.6–4.9 eV, much higher than those of SiC and GaN. β-Ga 2 O 3 has a high saturation electron velocity ( v s ) of 2 × 10 7 cm/s, which allows for high current density and high-frequency operation. , …”
Section: Introductionmentioning
confidence: 99%
“…In this work, to verify this straightforward exfoliation method, vdW epitaxy of Ga 2 O 3 membranes are conducted on the mica substrate, followed by vdW-bond-assisted exfoliation to transfer the Ga 2 O 3 membrane from the mica substrate to adhesive tape. Ultrawide band gap Ga 2 O 3 is examined specifically, owing to its superior properties, including large bandgap (≈5 eV), high critical breakdown field (≈ 8 MV/cm), and relatively high electron mobility, which has great potential in the applications of solar-blind photonics and high-power electronics. Moreover, except for the thermodynamically stable β-phase, Ga 2 O 3 has many other polymorphs, namely α, γ, δ, ε, and κ. For instance, the metastable κ-phase Ga 2 O 3 could have a high application potential owing to its unique spontaneous polarization property .…”
Section: Introductionmentioning
confidence: 99%
“…In earlier reports, Ga 2 O 3 thin films have been grown on bulk substrates such as sapphire, Si, and SiC. , These bulk substrates determine the lateral configuration of Ga 2 O 3 -based devices, such as the metal–semiconductor–metal (MSM) solar-blind photodetector (PD) and lateral field-effect transistor. , However, they also constrain the merits of Ga 2 O 3 owing to the long transition path of carriers in the lateral device configuration, which is generally a few micrometers to dozens of micrometers based on the photolithography resolution. , Instead, in this work, the proposed vdW-bond-assisted exfoliation provides the feasibility of vertical device configuration in Ga 2 O 3 membrane, allowing for applications such as vertical PD with short transition path of carriers and quick response of the devices. This electrical transition path is determined by the thickness of the Ga 2 O 3 membrane, which could be tens to hundreds of nanometers based on the growth design.…”
Section: Introductionmentioning
confidence: 99%
“…33 Tang et al reported the quasi-epitaxial growth of a b-Ga 2 O 3 -coated wide band gap semiconductor tape for flexible UV photodetectors. 34 Nanomembranes can be exfoliated from b-Ga 2 O 3 with a thickness less than 100 nm, 33 and Zhou et al reported their high performance on insulator field-effect transistors. 35 Interestingly, electronic and optoelectronic properties of novel Ga 2 O 3 monolayers can be tuned flexibly, 36 which can lead to applications in gas-sensing devices 37 and high-performance solar blind photodetectors based on two-dimensional gallium oxide monolayers.…”
Section: Introductionmentioning
confidence: 99%